mm - Hưng, Bùi Kiều; Luyến, Phan Thị; Quang, Lê Văn (TẠP CHÍ KHOA HỌC LÂM NGHIỆP, 2024)
(Amomum longiligulare T.L.Wu) , Phan Thị Luyến, Lê Văn Quang - Viện Khoa học Lâm nghiệp Việt Nam Từ khóa: TÓM TẮT , ra hoa, đ 4 (2kg 165,67cm, 47,42 nh -163,67cm , 8,67 q 49,07%). Keywords: Amomum longiligulare T.L.Wu, hill garden land, Ba Vi National Park Research on technique of planting Amomum longiligulare T.L.Wu on the hill garden land in the edge of Ba Vi National Park